Capital Structure, Risk, and Performance of Banks: Empirical Study of Ghana and Nigeria - Ishaya, Kwasau Jeremiah (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
This study examines the determinants of bank capital structure in Ghana and Nigeria. It also sought to investigate the linear relation between capital structure and risk (Beta) of banks in Ghana. A panel data of 7 listed commercial banks in Ghana was analyzed over a period of 2008-2012, using a generalized least squares technique to estimate fixed and random effect regression models. At the same time, a panel data of ten commercial banks in Nigeria was also analyzed over the same span but from 2007 to 2011 for lack of data on some banks in the year 2012. The results indicate that liquidity, operating expenses, and return on average equity are the significant determinant of Capital Structure for both countries. All the variables except return on average equity have a negative association with leverage in the case of Ghana whereas liquidity and operating efficiency have a negative relationship with leverage in the case of Nigeria. These results are in line with corporate finance theory such as Trade-off theory, Agency Cost, Pecking order theory and signaling effect. This will help analyst and financial managers to understand the dynamics of capital structure in the banking sector of Ghana and Nigeria. Keywords: Capital Structure, Profitability, Equity Risk, Ghana, Nigeria

ÖZ: Bu çalısmada, Gana ve Nijerya’daki bankaların sermaye yapılarını belirleyen faktörler incelenmistir. Ayrıca, Gana’daki bankaların, sermaye yapıları ve riskleri (Beta) arasındaki doğrusal iliskide incelenmistir. 2008-2012 yılları arasında faaliyet gösteren ve panel verisi seklinde listelenmis 7 ticari banka, genellestirilmis en küçük kare tahmincisi ve rastsal etkiler bağlasım modeli yöntemleriyle analiz edilmistir. Aynı zamanda, panel veri seklinde listelenmis Nijerya’daki 10 ticari banka, 2012’deki verilerin eksik olması nedeniyle aynı yöntemlerle ancak 2007-2011 yılları arasında incelenmistir. Sonuçlar her iki ülkede de, likidite, faaliyet giderleri ve öz sermayenin ortalama getirilerinin sermaye yapısını belirleyen ana faktörler olduğunu göstermektedir. Gana’daki bankalar için, öz sermayenin ortalama getirileri hariç diğer bütün değiskenlerin, Nijerya’daki bankalar içinse likidite ve faaliyet giderlerinin finansal kaldıraç ile negatif iliskisi saptanmıstır. Bu çalısmada bulunan sonuçlar, takas teorisi, temsil maliyeti, hiyerarsi ve sinyal etkisi gibi kurumsal finansman teorileriyle de uyumludur. Bu sonuçlar, Gana ve Nijerya’da bankacılık sektöründeki analizcilerin ve finans yöneticilerinin, sermaye yapısı dinamiklerini daha iyi anlamasına yardımcı olacaktır Anahtar Kelimeler: Sermaye yapısı, karlılık, özkaynak riski, Gana, Nijerya
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2014. Supervisor: Assoc. Prof. Dr. Eralp Bektaş.
Keywords: Banking and Finance; Banks and Banking - Ghana; Banks and Banking - Nigeria; Capital Structure; Profitability; Equity Risk; Ghana; Nigeria